Detection of Left Ventricular Regional Function in Asymptomatic Children with beta-Thalassemia Major by Longitudinal Strain and Strain Rate Imaging - Ali Bay; Osman Başpınar; Göksel Leblebisatan; Ali Seçkin Yalçın; Ahmet İrdem (Turkish Journal of Hematology, 2013)
Objective: Cardiac failure due to iron overload remains the most common cause of death in patients with beta-thalassemia major. This study aimed to evaluate myocardial function in children with beta-thalassemia major using standard echocardiography technique and strain rate imaging.